Identificación de caninos mandibulares para la determinación del sexo en el reconocimiento forense. - Illescas Fierro, Diego Mauricio (2025)
This study is based on a literature review regarding the use of the mandibular canine index for sex determination in forensic identification. The mandibular canine index has been recognized as an effective method for determining sex in forensic settings; however, variations in its reported accuracy have been noted. Given the high incidence of unidentified human remains in criminal cases and disaster scenarios, it is essential to re evaluate the effectiveness of reliable and accessible morphometric methods. Mandibular canines exhibit the highest degree of sexual dimorphism among dental structures, making them a reliable tool for the identification of human remains in situations where recognition is challenging. The primary focus of this research is to examine the mandibular canine index as a method for sex estimation through a bibliographic review of scientific literature. The PRISMA methodology was employed, resulting in the selection of 44 documents, including high-impact scientific journal articles, international journals, and academic theses from both national and international university repositories. The results indicate that the mesiodistal width of mandibular canines demonstrates a sex determination accuracy ranging from 74.2% to 87.5%, proving particularly useful in cases involving incinerated or fragmented human remains. The mandibular canine index represents a valid and accessible resource for supporting sex identification in forensic contexts. Collaboration between dental professionals and forensic institutions is essential for the effective and ethical application of this technique.